2018
DOI: 10.1111/pace.13287
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after upgrading from pacemakers to cardiac resynchronization therapy

Abstract: Background and aims: Right ventricular pacing may lead to heart failure (HF). Upgrades from pacemakers to cardiac resynchronization therapy (CRT) were excluded from most randomized, controlled trials. We sought to determine the long-term outcomes of upgrading from pacemakers to CRT with (CRT-D) or without (CRT-P) defibrillation in patients with no history of sustained ventricular arrhythmias. No group differences emerged in any of these endpoints after propensity score matching. After inverse probability weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
7
2
Order By: Relevance
“…Notably, not only the type of the implanted device but also the date of implantations might affect the outcomes due to the continuously improving device technology and drug treatment. However, neither the previously reported data 10 nor our results could confirm that the date of implantation has an impact on outcomes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Notably, not only the type of the implanted device but also the date of implantations might affect the outcomes due to the continuously improving device technology and drug treatment. However, neither the previously reported data 10 nor our results could confirm that the date of implantation has an impact on outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Leyva et al . observed a higher risk of mortality in upgrade patients receiving CRT-P devices than those being upgraded to a CRT-D. 10 Compared with our patient cohort, Leyva et al . included CRT upgrade recipients with no history of sustained ventricular arrhythmia, and they investigated the CRT upgrade in the context of primary prevention.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30] Bogale et al 19 investigated 692 patients with upgrades to CRT/CRT-D and 1675 patients with de novo CRT/CRT-D, with follow-up of approximately 1 year, and did not find significant differences in survival (P ¼ 0.57) between the 2 groups. Similar results were reported by a few other studies 21,23,24,29,30 with similarly short follow-up periods (ranging from reporting at 290 days to 4 years) or upgrades solely from pacemaker devices. Vamos et al 28 conducted an observational prospective study with an average follow-up of 37 months and reported higher mortality in upgraded patients compared with patients with de novo CRT implants (HR, 1.79; 95% CI, 1.08-2.95; P ¼ 0.023), whereas Cheung et al 20 reported that CRT upgrades were independently associated with increased mortality (adjusted odds ratio, 1.91; 95% CI, 1.67-2.19; P < 0.001) compared with de novo CRT implants.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes were compared with a population of adult patients with NICM or ICM who also underwent CRT device implantation in the same time period. Some adult patients with NICM or ICM have been included in previous publications . The study was approved by the Clinical Audit Department at the Queen Elizabeth Hospital, which permits publication of clinical data for the purposes of service evaluation.…”
Section: Methodsmentioning
confidence: 99%